Frege's conception of logic - Blanchette, Patricia (Oxford : Oxford University Press, 2012)
In this volume, Patricia A. Blanchette explores the relationship between Gottlob Frege's understanding of conceptual analysis and his understanding of logic.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Frege, Gottlob, -- 1848-1925.; Logic